JUSTICE COLLABORATOR IN THE CRIMINAL ACT OF PREDICTIVE MURDER (Study Of The Decision Of The South Jakarta District Court) (Number: 798/Pid.B/2022/PN.Jkt.Sel) - Ramlan Damanik; Mahmud Mulyadi; Rosmalinda (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Justice Collaborator (Cooperating Witness) is a suspect, defendant, or convict who cooperates with law enforcement to uncover a crime in the same case. Justice Collaborator has a big role in uncovering certain crimes. Justice Collaborator also played a role in uncovering the premeditated murder case against Victim NYH who was an aide to FS who served as Head of Propam Division of the National Police Headquarters. The initial chronology presented in the police report after the incident was not premeditated murder, but rather a shooting incident between the Victim and another aide, namely RE. However, thanks to RE's courage in volunteering as a Justice Collaborator, the premeditated murder crime that occurred has been uncovered. This study discusses the problem of how the practices of determining justice collaborators in Indonesia, how the determination of justice collaborators on behalf of RE in the crime of premeditated murder, and how the legal considerations of the Panel of Judges in imposing criminal sanctions on justice collaborators on behalf of RE. The research method in this thesis uses a research method with a normative research type with a descriptive analytical research nature and a qualitative data analysis method, by examining the Decision of the South Jakarta District Court Number: 798/Pid.B/2022/PN. Jkt.Sel and laws and regulations and other legal materials related to the determination of justice collaborators in premeditated murder. The practice of determining Justice Collaborators in Indonesia is carried out based on the provisions of laws and regulations, including Law Number 31 of 2014 and SEMA Number 4 of 2011 with the requirements for determining justice collaborators, namelyjustice collaboratoris one of the perpetrators of a particular crime or a particular criminal case that he committed, not the main perpetrator in the crime and provided information as a witness in the trial process. Then against the Justice collaborator on behalf of RE who is the executor in the crime of premeditated murder, was determined as a justice collaborator with the consideration that the crime of premeditated murder he committed met the qualifications of a "certain case" with the indicator being another crime that resulted in the position of the witness and victim being faced with a very life-threatening situation and the fulfillment of the requirement that the justice collaborator in this decision is not the main perpetrator. For his role as a justice collaborator, RE was given a light sentence with a prison sentence of 1 (one) year and 6 (six) months with one of the considerationsThe victim's family has forgiven the defendant.